Distribution of the Most Prevalent Spa Types among Clinical Isolates of Methicillin-Resistant and -Susceptible Staphylococcus aureus around the World: A Review - Asadollahi, Parisa; Farahani, Narges Nodeh; Mirzaii, Mehdi; Khoramrooz, Seyed Sajjad; van Belkum, Alex; Asadollahi, Khairollah; Dadashi, Masoud; Darban-Sarokhalil, Davood (Frontiers in Microbiology, 2018)
Background: Staphylococcus aureus, a leading cause of community-acquired and nosocomial infections, remains a major health problem worldwide. Molecular typing methods, such as spa typing, are vital for the control and, when typing can be made more timely, prevention of S. aureus spread around healthcare settings. The current study aims to review the literature to report the most common clinical spa types around the world, which is important for epidemiological surveys and nosocomial infection control policies. Methods: A search via PubMed, Google Scholar, Web of Science, Embase, the Cochrane library, and Scopus was conducted for original articles reporting the most prevalent spa types among S. aureus isolates. The search terms were “Staphylococcus aureus, spa typing”. Results: The most prevalent spa types were t032, t008 and t002 in Europe; t037 and t002 in Asia; t008, t002 and t242 in America; t037, t084, and t064 in Africa; and t020 in Australia. In Europe, all the isolates related to spa type t032 were MRSA. In addition, spa type t037 in Africa and t037and t437 in Australia also consisted exclusively of MRSA isolates. Given the fact that more than 95% of the papers we studied originated in the past decade there was no option to study the dynamics of regional clone emergence. Conclusion: This review documents the presence of the most prevalent spa types in countries, continents and worldwide and shows big local differences in clonal distribution.